Analisis Pengaruh Pengelolaan SDM Terhadap Kinerja Karyawan Pada PT ASKRINDO Cabang Surakarta - Rina S Sinar (Jurnal Ilmiah Poli Bisnis, 2021)
The key to the succes of a company lies in the human resources also applies of PT ASKRINDO (Indonesian Credit Insurance) Surakarta Branch. since today, there are many phenomena of low employee performance working in a company, so this study aims to see the effect of human resources management on employee performance at PT ASKRINDO Surakarta Branch. Good human resources management will improve the quality of employee performance at PT ASKRINDO Surakarta Branch. This study used qualitative methods and data were obtained from interviews with informants consisting of 8 employee of PT ASKRINDO Surakarta Branch and various literature reviews as a method of data collection. The results showed that human resources management was proven to have an effect on employee performance at PT ASKRINDO Surakarta Branch with several indicators on human resources management; human resource procurement, human resource development, career development, job performance appraisal, compensation, worker safety and health, and job analysis and design. So, with an increase in human resource management will improve the performance of employees at PT ASKRINDO Surakarta Branch.